Well-being of adult adoptees in Iceland - Hildur Ósk Gunnlaugsdóttir 1988- (2018)
In the present study the well-being of adult adoptees was examined. The purpose was to examine whether difficulties with separation anxiety, attachment, depression, anxiety, bullying, taunting and satisfaction with life were present when adoptees reach adulthood. It has been found that adopted children often present difficulties with attachment and separation, fear of rejection as well as mental health problems. The participants were 120 adult adoptees that were contacted through Facebook. They received a questionnaire via email that included a number of questions about their origin, bullying and taunting as well as questionnaires on romantic attachment (The multi-item measure of adult romantic attachment; MMARA), separation anxiety (The adult separation anxiety-27; ASA-27), depression (The patient health questionnaire-9; PHQ-9), anxiety (The generalized anxiety disorder-7; GAD-7) and life satisfaction (The satisfaction with life scale-5; SWLS-5). One-way ANOVA was used to examine the effects of birthplace on those lists, e.g. MMARA, ASA-27, PHQ-9, GAD-7 and SWLS-5. Linear regression was used to examine whether gender, age, country of origin, well-being in school and work both as a child an as an adult, bullying and wanting to know more about origin could account for the variance in participants’ scores on the ASA-27 questionnaire and the anxiety subscale of the MMARA. The results indicate that adult adoptees experience difficulties with being separated from their loved ones and that they are more prone to forming anxious attachment when in romantic relationships. Results also indicate that gender, well-being in school as a child, well-being in work/school as an adult and wanting to know more about one’s origin are related to difficulties with separation and attachment. These findings suggest that difficulties with seperation and attachment that rise during childhood may also be present in adulthood.